Genomic conservation and putative downstream functionality of the phosphatidylinositol signalling pathway in the cnidarian-dinoflagellate symbiosis - Ashley, Immy A.; Kitchen, Sheila A.; Gorman, Lucy M.; Grossman, Arthur R.; Oakley, Clinton A.; Suggett, David J.; Weis, Virginia M.; Rosset, Sabrina L.; Davy, Simon K. (Frontiers in Microbiology, 2023)
The mutualistic cnidarian–dinoflagellate symbiosis underpins the evolutionary success of stony corals and the persistence of coral reefs. However, a molecular understanding of the signalling events that lead to the successful establishment and maintenance of this symbiosis remains unresolved. For example, the phosphatidylinositol (PI) signalling pathway has been implicated during the establishment of multiple mutualistic and parasitic interactions across the kingdoms of life, yet its role within the cnidarian-dinoflagellate symbiosis remains unexplored. Here, we aimed to confirm the presence and assess the specific enzymatic composition of the PI signalling pathway across cnidaria and dinoflagellates by compiling 21 symbiotic anthozoan (corals and sea anemones) and 28 symbiotic dinoflagellate (Symbiodiniaceae) transcriptomic and genomic datasets and querying genes related to this pathway. Presence or absence of PI-kinase and PI-phosphatase orthologs were also compared between a broad sampling of taxonomically related symbiotic and non-symbiotic species. Across the symbiotic anthozoans analysed, there was a complete and highly conserved PI pathway, analogous to the pathway found in model eukaryotes. The Symbiodiniaceae pathway showed similarities to its sister taxon, the Apicomplexa, with the absence of PI 4-phosphatases. However, conversely to Apicomplexa, there was also an expansion of homologs present in the PI5-phosphatase and PI5-kinase groups, with unique Symbiodiniaceae proteins identified that are unknown from non-symbiotic unicellular organisms. Additionally, we aimed to unravel the putative functionalities of the PI signalling pathway in this symbiosis by analysing phosphoinositide (PIP)-binding proteins. Analysis of phosphoinositide (PIP)-binding proteins showed that, on average, 2.23 and 1.29% of the total assemblies of anthozoan and Symbiodiniaceae, respectively, have the potential to bind to PIPs. Enrichment of Gene Ontology (GO) terms associated with predicted PIP-binding proteins within each taxon revealed a broad range of functions, including compelling links to processes putatively involved in symbiosis regulation. This analysis establishes a baseline for current understanding of the PI pathway across anthozoans and Symbiodiniaceae, and thus a framework to target future research.